The Effectiveness of Rotation of Stations Model for Blended learning in Developing the Creative Thinking Skill "Evaluating and Improving Ideas" in the Light of the PISA Framework for Mathematics Among Second- Grade Students - Alsulmi, Amerh Owud Onallah (Journal of Curriculum and Teaching Methodology, 2023)
This study aimed at searching the effectiveness of rotation of stations model for blended learning in developing the creative thinking skill "evaluating and improving ideas" in the light of the PISA framework for mathematics among second- grade students. The research sample consisted of (76) students from second- grade students in the eighteenth after hundred school in Jeddah. The research used the quasi- experimental approach. They were randomly divided into two groups: the controlled group and experimental group. A creative thinking skill development test “evaluation and development of ideas” was used. The researcher reached the following findings: (1) The improvement in the levels of creative thinking skill "evaluating and improving ideas" in the light of the PISA framework for mathematics of experimental group in the post test is due to the use of the rotation of stations model for blended learning, which is large and exceeds 80%. (2) The rotation of stations model for blended learning is keeping up with the era developments and provide interactive communication between teachers and learners. (3) Creativity in mathematics is represented in producing unprecedented relationships and providing new solutions to mathematical problems, provided that there are no criteria for right or wrong. This requires raising the efficiency of the methods in which mathematics is taught, in order to develop the skill of creative thinking skill "evaluating and improving ideas" in the light of the PISA framework for mathematics
Keywords: Effectiveness; Rotation of Stations Model; Blended Learning; Creative thinking skill; PISA